Wednesday
March 29, 2017

Post a New Question

Posted by on .

Calculus - Reiny, Friday, December 23, 2011 at 6:59pm
I read that as
(4a^2-1)/(4a^2-16) * (2-a)/(2a-1) , my brackets are necessary
= (2a+1)(2a-1)/( 4(a+2)(a-2) * (2-a)/(2a-1)
the (2-a)/(a-2) are opposite, they will give you the -1
so..
= -(2a+1)/(4(a+2)) , again you have to use brackets to write it on here.



Calculus - -Untamed-, Saturday, December 24, 2011 at 5:17pm
Thanks Reiny =) But I to get everything clear, the 2-a and the a-2 cancel right? After I cancel those I am left with (2a+1) as the numerator:S Sorry I am just confused. Also did you factor out the 2a+4 and 2a-4 to get 4(a+2)(a-2)? Could you please explain step by step?

  • Calculus--Reiny - ,

    (2a+1)(2a-1)/( 4(a+2)(a-2) * (2-a)/(2a-1)

    (2a+1)(2a-1) (2-a)
    ====================
    4(a+2)(a-2)(2a-1)


    (2a+1)(2a-1) (2-a)
    ====================
    4(a+2)(-1)(2-a)(2a-1)

    -(2a+1)(1) (2-a)
    ====================
    4(a+2)(2-a)(1)

    -(2a+1)(1) (1)
    ====================
    4(a+2)(1)(1)

    -(2a+1)
    ====================
    4(a+2)

  • Calculus--Reiny - ,

    Thanks Damon =)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question